e-Business and Telecommunications 6th International Joint Conference, ICETE 2009, Milan, Italy, July 7-10, 2009. Revised Selected Papers - Obaidat, Mohammad S.; Filipe, Joaquim; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 6th International Joint Conference on e-Business and Telecommunications, ICETE 2009, held in Milan, Italy, in July 2009. The 34 revised full papers presented together with 4 invited papers in this volume were carefully reviewed and selected from 300 submissions. They have passed two rounds of selection and improvement. The papers are organized in topical sections on e-business; security and cryptography; signal processing and multimedia applications; wireless information networks and systems.
Keywords: Computer science; Computer Communication Networks; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Computer Science; Computer Communication Networks; e-Commerce/e-business.; Data Structures, Cryptology and Information Theory; Coding and Information Theory; Data Encryption; Mathematical Logic and Formal Languages